Nature of Sexual Harassment Against the Female Students of Bangladesh: A Cross-Sectional Study in Tangail Municipality - Khan, Md. Bashir Uddin; Shathi, Israt Jahan (International Journal of Social and Administrative Sciences, 2018)
Attitude towards women and girls in many cases is liable for making them vulnerable to sexual harassment. Bangladesh as a south Asian country in many cases could not keep it away from such unexpected criminal outbreaks. Patriarchal attitude, disorganized social system, unplanned settlement and lack of social control provoke probable offenders to be involved in such repugnant activities. In this context, this study was an effort to understand the nature of sexual harassment through which the female students of different institutions of Tangail municipality generally undergo. This research included four educational institutions from this municipality and selected those institutions purposively. Primary data for this study then were collected with a pre-set questionnaire within the month of February to April 2017. A number of 120 female students of the selected institutions were, therefore, interviewed to understand the nature of sexual harassment experienced by them and their intimates. The study finds that most of the students were the victims of such incidents at least for once in their lives and most of them were victimized in the locations that are outside of their educational institutions. The study also reveals that these incidents or experiences of their own and that of others have generated a considerable fear among them. Therefore, such incidents of harassment put an impact on their academic and social life with dreadful psychological consequences. For preventing such offensive actions, most of the female students insisted on strict law enforcement process so that it can have a deterrent impact on the society.